Analisis Dampak Terhadap Anak Hasil Perkawinan Beda Negara dalam Berpartisipasi Kegiatan Berskala Nasional - Devarra Qeentarizha Prayoga; Dimas Dwi Nugroho; Geza Arditya; Pradipa Saraswati Annafi'Ah; Thariq Hanif Muhammad Kautsar (Jurnal Relasi Publik, 2023)
Every year on august 17th is commemorated as Indonesia’s independence day. Representatives of young people from all corners of the country gather at Istana Merdeka to hoist the Bendera Merah Putih. However, in the year 2016, an unpleasant incident occurred for the world of Pakibraka. Indeed, a national Paskibraka member named Gloria Natapradja Hamel had to be dismissed shortly before the flag-raising, as she held dual citizenship. Peraturan Menpora nomor 0065 tahun 2015 and Undang-Undang nomor 12 tahun 2006 directly impact every child who born with dual citizenship, causing limitations in their participation in national-scale activities, in this case, the National Paskibraka. This research is expected to contribute to the development of international civil law, especially regrading the rights of children restricted by it.